Mexican Paper - The Operation of the "Hole-Contract" System in the Center Star and War Eagle Mines, Rossland, B. C. (Discussion, 1005) - Carl R. Davis (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1902)
The cost of mining during the past history of these mines has been excessive, principally by reason of the inefficiency of labor under the wage-system. The amount of labor performed per man was unsatisfactory; and Mr. Edmund B. Kirby, the general manager, decided to adopt the contract-system as a remedy. For this purpose the method now in use was devised by the writer (then and now the superintendent), as best adapted to the local conditions. On March 12, 1900, this system was presented to the miners of the War Eagle and the Center Star. The issue remained unsettled for several weeks,